CHARACTERISTICS OF CIKEMBAR ZEOLITE AND ITS UTILIZATION EVALUATION - Julian Chyller Makabori, Hans
Zeolite is a multi-purpose non-metallic mineral because it has unique properties as an absorbent, molecular sieving, ion exchanger and catalyst. The potential of zeolite in Indonesia is spread across Sumatra, Java, Nusa Tenggara and Sulawesi. Cikembar, Sukabumi, West Java as one of zeolite potential areas has 24,151,000 ton of zeolite resources. Zeolite Cikembar until now is utilized as construction materials, mixed materials of animal feed and fertilizer. Because of that, research has been done to find out the chemical composition, type of zeolite, characteristics and evaluation of the utilization of Cikembar zeolite in order to provide recommendations for the utilization of Cikembar zeolite in the future. The chemical composition of Cikembar zeolite based on X-Ray Fluorescence (XRF) analysis id dominated by SiO2 and Al2O3 with a percentage of 73.04% and 12.67% repectively and there are also some other component in little amount such as Fe2O3, MgO, CaO, Na2O and K2O. From the X-Ray Difraction (XRD) analysis, it was found that the type of zeolite in Cikembar deposits is mordenit. Brunauer-Emmett-Teller (BET) analysis obtained that the specific surface area of the Cikembar zeolite is 12,162 m2/g and cation exchange capacity (CEC) analysis obtained that CEC value of Cikembar zeolite is 68.60 meq/100 g. Based on the chemical composition and the type of zeolite mineral in Cikembar deposits, the Fe2O3 content can be interpreted as impurity while Na2O, CaO and K2O more likely come from mordenite extra framework components. By comparing the characterics of Cikembar of Cikembar zeolite to other zeolite deposit in cikalong, Tasikmalaya as a reference, it can be envisaged that zeolite Cikembar can also be used in water and waste processing industry by physical and chemical activation process to obtain cation exchange capacity value (CEC) and higher adsorbs capability.